Pengaruh Capital Intensity, Inventory Intensity, dan Sales Growth terhadap Tax Avoidance pada Perusahaan Manufaktur - Dwi Fara; Ria Rachmawati; Rohmaniyah Rohmaniyah; Nurul Alfian (Politeknik Ganesha Medan, 2026)
This study investigates the influence of capital intensity, inventory intensity, and sales growth on tax avoidance among manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. Tax revenue represents a primary source of government income; however, companies frequently employ tax avoidance mechanisms to reduce their fiscal obligations. Firm characteristics, particularly asset composition and revenue growth, are regarded as important factors that may influence a company’s tendency to engage in tax avoidance practices. The population of this study consists of 98 companies observed during the 2022–2024 period. Through a purposive sampling technique, 44 companies that met the research criteria were selected as the sample. The data used are secondary data obtained from the companies’ annual financial statements. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS Version 26. The results indicate that capital intensity has a positive effect on tax avoidance, as companies with a higher proportion of fixed assets can utilize depreciation expenses to reduce taxable income. In contrast, inventory intensity does not show a significant effect on tax avoidance. Sales growth has a positive and statistically significant influence, meaning that companies experiencing higher revenue growth are more likely to implement tax management strategies to reduce their increasing tax liabilities.